Perancangan Desain User Interface Mobile Apps Pada Sistem Penanggulangan Gawat Darurat Terpadu D.I.Y - dwi nugroho (Minat Sistem Informasi Manajemen Kesehatan Fakultas Kedokteran UGM, 2022)
Background: Emergency incidents that occur in Indonesia are increasing day by day, both emergency incidents due to traffic accidents and incidents due to disease. The Indonesian government issued PERMENKES number 19 of 2016 concerning the Integrated Emergency Management System, in the creation of the SPGDT it is expected to be able to handle emergency cases in an integrated manner so as to minimize cases of disability and death. The Yogyakarta Special Region Health Service is currently running well in the implementation of SPGDT, but currently, the SPGDT application does not have the Mobile-Apps feature, especially on the Tracking Ambulance menu. With the ambulance tracking menu, people can easily make ambulance calls based on emergency cases that occur and also people don't need to worry if they find an emergency incident but the ambulance doesn't come, with ambulance tracking people can also see the movement of an ambulance that is on